RELIGIUSITAS UMAT ISLAM SETELAH KONVERSI KE HINDU DALAM MENJALANKAN UPACARA DEWA YADNYA - I Ketut Manik Asta Jaya (UHN IGB Sugriwa Denpasar, 2022)
This study aims to examine more deeply related to the religiosity of Muslims after conversion to Hinduism in Nyitdah Village, Kediri District, Tabanan Regency. Respondents in this study were Hindus who had previously undergone the Sudhi Wedani ceremony procession to continue at the wedding stage. This study uses a descriptive qualitative method, this method is used to examine the status of a group of people, an object, a set of conditions, a system of thought, or a class of events in the present. The results of this study show that after becoming Hindus, they are able to carry out a number of religious rituals, even though before they were Muslims, which was far from the aspect of ceremonial rituals. Especially in carrying out ceremonies related to Yadnya gods, starting from carrying out the Tri Sandya Puja to making ceremonial facilities such as canangs to making offerings for piodalan ceremonies. The results of this study also note that not all respondents are able to properly make ceremonial facilities, such as piodalan banten. There are still respondents who are in the learning stage of making various ceremonial facilities. However, the majority of respondents have been able to make canangs to carry out puja tri sandhya.